THE EFFECT OF WORK MOTIVATION AND COMPENSATION ON THE PERFORMANCE OF PT TAMACO GRAHA KRIDA EMPLOYEES MOROWALI DISTRICT - Djibran, Moch Aedil; Natsir, Syahir; Santi, Ira Nuriya (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2021)
This study aims to 1) determine the effect of work motivation and compensation on theperformance of employees of PT Tamaco Graha Krida Morowali Regency. 2) determine theeffect of motivation on the performance of employees of PT. Tamaco Graha Krida MorowaliRegency. 3) determine the effect of compensation on employee performance of PT. TamacoGraha Krida Morowali Regency. The object of this research is Motivation, compensation andemployee performance. The results of the study concluded that together they had a significanteffect on the performance of employees of PT Tamaco Graha Krida Morowali Regency. Thusmotivation and compensation at the company PT. Graha Krida Morowali Regency, willprovide an increase in employee performance. This shows that if motivation and compensationundergo changes, in relation to motivation, and compensation, will have a positive impact onemployee performance, reflecting motivation and compensation can have a positive influence,on improving employee performance. This shows that if the company PT Graha KridaMorowali Regency makes changes to motivation and compensation will have a positive impacton improving employee performance.Keywords: Motivation, Compensation, and Employee Performance